An Act to Reduce the Law Incorporating the City of Madison, and the Several Acts Amendatory thereto into One Act, and to Amend the Same, 1847 Ind. Acts 93, chap 61, § 8, pt. 4 - (:unkn) unknown (General Publisher, 1847)
Authorized the town of Madison to regulate and license the keepers of gunpowder and other explosive compounds
--
Keywords: GUN POWDER STORAGE